Pengembangan Smart Home Dengan Microcontrollers ESP32 Dan MC-38 Door Magnetic Switch Sensor Berbasis Internet of Things (IoT) Untuk Meningkatkan Deteksi Dini Keamanan Perumahan - Andi Setiawan; Ade Irma Purnamasari (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The objective developed from this research is to utilize Smart Home with an integrated ESP32 microcontroller with a camera and MC-38 door magnetic switch sensor based on the Internet of Things (IoT) as a research base to detect the security of arumsari earth housing in Cirebon District when left by its inhabitants. ESP32 microcontroller which can be programmed via arduino IDE, then functioned to respond to the integrated camera so that it can transmit images when the MC-38 sensor door magnetic switch sensor is active. Technically the combination of the ESP32 microcontroller and MC-38 door magnetic switch sensor, which was developed as a prototype in this study is called the arumsari housing early detection system. The mechanism of the arumsari housing early detection system is when a house door or window is successfully forcibly broken without going through the system mechanism, then automatically an image or can also be developed into a video from a camera mounted on an ESP32 microcontroller will send the image through a web framework or smartphone as a form early warning of security to housing owners. The results obtained from this study are at the angle of normally open MC-38 door magnetic switch sensor of 60 - 1800, will work sending an image signal which means there is an indication of a burglar or unknown person entering the house. Whereas at the normally closed angle MC-38 door magnetic switch sensor is 00-50, it will not work sending an image signal which means the house is safe.